FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KUALITAS KINERJA PEGAWAI DI KANTOR KELURAHAN MACORAWALIE KECAMATAN PANCARIJANG - A, Nurul Muhliza; Adnan, Andi Astinah; Mannu, Ahmad (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This study aims to examine what factors affect the quality of employee performance in the macorawalie village office. The type of research used in this research is a quantitative approach. The population of this study was 87 people. The questionnaire is a data collection technique used with data analysis techniques, namely IBM SPSS Statistics 26. based on the results of variable recapitulation of internal factors and external factors with a percentage of 71.75%% in the good category and variable recapitulation of employee performance quality with a result of 75.2% in the expected good category. In addition, the factors that affect the quality of employee performance in the macorawalie village office, Pancarijang sub-district are "Influential / Significant". From the results of the Aanova test, it was found that F was 14.360 with a significant level of 0.000, this shows that the independent variable has a significant effect and the probability is far from above 0.05 individually t count 3.789 ≥ t table 1.663, meaning that the factors that influence / significant on the quality of employee performance at the Mocorawalie Village Office, Panca Rijang sub-district.